A 3D Finite Element Model for Investigating Effects of Refurbishing on Rolling Contact Fatigue. Issue 2 (3rd March 2020) - Golmohammadi, Zamzam; Sadeghi, Farshid
Abstract: A 3D finite element (FE) model was developed to investigate the effects of refurbishing on rolling contact fatigue (RCF) behavior of through-hardened bearing steel in a circular contact. In this investigation, the material degradation due to fatigue in original and refurbished domains was modeled using continuum damage mechanics (CDM). Material damage, crack initiation, and propagation in a circular contact were modeled to estimate the fatigue life of original and refurbished domains using CDM. RCF lives of pristine domains were predicted to define the baseline for the through-hardened steel. Then, a layer of material was removed to simulate the refurbishment while the accumulated damage for a set number of contact cycles was preserved in the domain. The refurbished domains were subjected to RCF cycles using the 3D FE model until a crack reached the surface indicating final life. A parametric study was conducted to evaluate the influence of material removal depth, loading cycles before refurbishing, applied load, and spall formation in the circular contact. The model results demonstrated that refurbishing increased fatigue life. Higher fatigue cycles before refurbishing and greater regrinding depth enhanced the total fatigue life. Furthermore, as expected, increasing the applied load reduced the fatigue life extension of restored domains.